Prenatal alcohol consumption and infant and child behavior: evidence from the Growing Up in New Zealand Cohort - Schoeps, Anja; Peterson, Elizabeth R.; Mia, Yasmine; Waldie, Karen E.; Underwood, Lisa; D'Souza, Stephanie; Morton, Susan M. B. (Early human development, 2018)
Background - High levels of alcohol exposure during pregnancy can damage developing brains and influence child behavior and learning. - Aim - To examine the effects of lower levels of alcohol and very early exposure to alcohol on infant temperament and child behavior. - Study design, subjects, and outcome measures - The Growing Up in New Zealand study involves a prospective birth cohort of 6822 pregnant women of whom 6156 provided information on their child's temperament using the Infant Behavior Questionnaire-Revised (IBQ-R VSF) at 9months and their child's behavior using the Strengths and Difficulties Questionnaire at 2years. - Results - A series of adjusted linear regression models controlling for socio-demographic factors found alcohol consumption during pregnancy was most consistently related to Lower Positive Affect, Affiliation/Regulation, and Orienting Capacity temperament scores. Mothers who stopped drinking after becoming aware of their pregnancy, but had an unplanned pregnancy (hence may have a baby exposed to alcohol for longer), also reported infants with lower Orienting Capacity, Affiliation/Regulation, and Fear temperament scores compared to those that did not drink. Children whose mothers drank four or more drinks per week during pregnancy were more likely to report their child as having conduct problems, with higher total difficulties scores at age 2. - Conclusions - Alcohol consumption during pregnancy has a negative effect especially on infant temperament, even if small amounts of alcohol are consumed. Our findings have implications for men and women who drink, medical professionals, and for the availability of contraception to those who drink, but do not plan to get pregnant.
Gesehen am 22.04.2020